Objective criteria of the axial and refractive components in the modified classification for distinguishing among axial, refractive, mixed and combinatory myopias proposed based on the analysis of morphometric parameters of myopic and emmetropic eyes - O.V. Maliieva; N.M. Bushuieva (Ukrainian Society of Ophthalmologists, 2021)
Background: Myopia is heterogeneous with regard to its origin and varies in its course and prognosis of sequelae. The lack of criteria does not allow in practice to distinguish among different types of the disease. Purpose: First, to study morphometric parameters characterizing the axial and refractive components (the axial length (AL) and corneal refractive power (CRP)) in myopes and emmetropes, and; second, to develop the criteria for selecting the ranges for axial, refractive, mixed and combinatory myopias based on the statistical analysis of AL and CRP. Material and Methods: Two hundred and sixty four patients (502 eyes) with various severities of myopia (mean myopic refractive error, -2.74 ± 2.41 D) and 78 emmetropes (145 eyes) were included in the study. Patients underwent visual acuity assessment for distance; autokeratorefractometry; measurement of horizontal pupil diameter and horizontal corneal diameter; ultrasonography of the posterior and anterior segments of the eye for AL, anterior chamber depth, and lens thickness measurements and pachymetry; and uncorrected intraocular pressure (IOP) and IOP corrected for pachymetry measurements. Results: The objective limits for different types of myopia were calculated based on the axial component (AL, 24.3 mm) and refractive component (CRP, 43.86 D). The newly developed objective criteria allow for establishing the type of myopia corresponding to axial and refractive components on the basis of corneal refractive power and axial length of the eye. The proposed modified classification of the types of myopia takes in account the axial and refractive components and allows for distinguishing practically among refractive myopia (AL ≤ 24.3 mm and CRP > 43.86 D), axial myopia (AL > 24.3 mm and CRP ≤ 43.86 D), mixed myopia (AL > 24.3 mm and CRP > 43.86 D), and combinatory myopia (AL ≤ 24.3 mm and CRP ≤ 43.86 D, similar to emmetropes).